Horizontal distribution of dinoflagellate cycts in surface sediments of Sungai Genting, Kelantan - Weng, Chan Kian (Fakulti Maritim dan Sains Marin, 2011)
Surface sediments were collected from 18 sampling points in a Kelantan coastal lagoon, Sungai Geting during pre-monsoon (July) and monsoon (December) seasons in 2004 to study dinoflagellate cyst species composition, abundance, distribution and their relationships to environmental parameters measured. Twenty-one species including one unidentified species of dinoflagellate cysts representing 11 genera of two orders (Gonyaulacales and Peridiniales) were identified in the study.